2019
DOI: 10.3389/fnins.2019.01156
|View full text |Cite
|
Sign up to set email alerts
|

Bioscaffold-Induced Brain Tissue Regeneration

Abstract: Brain tissue lost after a stroke is not regenerated, although a repair response associated with neurogenesis does occur. A failure to regenerate functional brain tissue is not caused by the lack of available neural cells, but rather the absence of structural support to permit a repopulation of the lesion cavity. Inductive bioscaffolds can provide this support and promote the invasion of host cells into the tissue void. The putative mechanisms of bioscaffold degradation and its pivotal role to permit invasion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 199 publications
1
38
0
Order By: Relevance
“…Interestingly, some cells are infiltrating into the hydrogel on the first day. This phenomenon is similar to the Ghuman's (Ghuman et al, 2018) study, who suggested that these cells are not a brain origin, but likely an immune origin (Modo, 2019), which was responding quickly to the damaged tissue.…”
Section: The Overall Change Of the Gelatin Hydrogel After Injectionsupporting
confidence: 86%
“…Interestingly, some cells are infiltrating into the hydrogel on the first day. This phenomenon is similar to the Ghuman's (Ghuman et al, 2018) study, who suggested that these cells are not a brain origin, but likely an immune origin (Modo, 2019), which was responding quickly to the damaged tissue.…”
Section: The Overall Change Of the Gelatin Hydrogel After Injectionsupporting
confidence: 86%
“…The consequences of AIS are hypoxia, an increase in radical oxygen species, and an excessive inflammatory response, which can lead to long-term consequences [ 220 , 221 ]. AIS leads to a loss of brain tissue, which is not regenerated, even if neurogenesis partially occurs, and this is due to the lack of structural support and the fact that the tissue undergoing injury creates a boundary to avoid damage expansion into the healthy tissue [ 222 ]. It is for this reason that bio-scaffolds could prove useful for the therapy of this disease, providing structural support [ 222 , 223 ].…”
Section: The Role Of Scaffolds In Developing Regenerative Therapiementioning
confidence: 99%
“…AIS leads to a loss of brain tissue, which is not regenerated, even if neurogenesis partially occurs, and this is due to the lack of structural support and the fact that the tissue undergoing injury creates a boundary to avoid damage expansion into the healthy tissue [ 222 ]. It is for this reason that bio-scaffolds could prove useful for the therapy of this disease, providing structural support [ 222 , 223 ]. The first evidence that supported the potentiality of scaffold use in AIS was determined after the transplantation of NSCs on polymeric scaffolds, with promising results [ 159 , 160 , 161 , 162 ].…”
Section: The Role Of Scaffolds In Developing Regenerative Therapiementioning
confidence: 99%
See 1 more Smart Citation
“…These are more easily able to mimic the appropriate microenvironments of transplanted cells, and therefore can improve survivability and promote differentiation of transplanted cells. Further, if a large section of cerebral parenchyma is lost, the substrates evoking the biological effects of therapy, such as rehabilitation, are also lost, meaning de novo functional tissue is necessary [28,29]. Therefore, optimizing the microenvironment of the transplantation site is considered essential for the success of cell therapy ( Figure 2).…”
Section: Cell Therapy For Stroke Recoverymentioning
confidence: 99%